1997
DOI: 10.1103/physrevlett.78.1026
|View full text |Cite
|
Sign up to set email alerts
|

Isospin Dependence of the Balance Energy

Abstract: The energy at which collective transverse flow in the reaction plane disappears, the balance energy E bal , is found to depend on the isospin of the system using the reactions 58 Fe 1 58 Fe and 58 Ni 1 58 Ni. The more neutron-rich system exhibits higher balance energies for all measured impact parameters, in agreement with the predictions of a transport model which incorporates an isospin dependent mean field and isospin dependent in-medium nucleon-nucleon cross sections.[S0031-9007 (97)02358-2] PACS numbers: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 37 publications
4
57
1
Order By: Relevance
“…Furthermore, the so-called balance energy where the transverse flow changes sign should also be sensitive to the isospin asymmetry of the reaction system. These predictions were soon verified by experiments carried out by Pak et al at NSCL/MSU [549,550]. One normally measures the strength of the transverse flow using the flow parameter F defined as the slope of the transverse momentum distribution at the center of mass rapidity y cm .…”
Section: Isospin Dependence Of Nucleon Transverse Elliptical and Radmentioning
confidence: 74%
“…Furthermore, the so-called balance energy where the transverse flow changes sign should also be sensitive to the isospin asymmetry of the reaction system. These predictions were soon verified by experiments carried out by Pak et al at NSCL/MSU [549,550]. One normally measures the strength of the transverse flow using the flow parameter F defined as the slope of the transverse momentum distribution at the center of mass rapidity y cm .…”
Section: Isospin Dependence Of Nucleon Transverse Elliptical and Radmentioning
confidence: 74%
“…Isospin effects of various physical phenomena, such as multifragmentation, collective flow, preequilibrium nucleon emission, etc., have been reported [1,8,9,10,11,12,13,14]. These studies have shown that isospin effect exists in nuclear reactions induced by exotic nuclei but it may disappear under some conditions.…”
Section: Introductionmentioning
confidence: 95%
“…The rapid advance in nuclear reactions using rare isotopes has opened up several new frontiers in nuclear science [1,2,3,4,5,6]. In particular, the intermediate energy heavy rare isotopes currently available at National Superconducting Cyclotron Laboratory (NSCL/MSU) and the future new facilities RIA in USA and SIS-200 at GSI in Germany provide a unique opportunity to explore novel properties of dense neutron-rich matter that was not in reach in terrestrial laboratories before.…”
mentioning
confidence: 99%